О cибирской косуле Сapreolus pygargus Рallas, 1771 на Украине: анализ митохондриальной и ядерной ДНК - Данилкин, А. А.; Плахина, Д. А.; Звычайная, Е. Ю.; Домнич, А. В.; Холодова, М. В.; Сорокин, П. А.; Волох, Анатолій Михайлович; Волох, Анатолий Михайлович; Volokh, Anatolii (My University, 2017)
RU: Проведен молекулярно-генетический анализ нуклеотидных последовательностей гена цитохрома b (1140 пар нуклеотидов) митохондриальной (мт) ДНК и 17 микросателлитных локусов восьми образцов мышечной ткани косуль из Самарского леса Днепропетровской обл. Украины. Для сравнения в исследование включены 212 соответствующих последовательностей мтДНК сибирской и европейской косуль и данные по изменчивости микросателлитных маркеров у 49 представителей этих видов. Отмечено, что все проанализированные митохондриальные последовательности особей из Самарского леса характерны для сибирской косули Capreolus pygargus Pallas, 1771. Описаны четыре гаплотипа, причем все они относятся к гаплогруппе, типичной для западной части ареала C. pygargus. Фрагментный анализ микросателлитных локусов ядерной ДНК подтвердил принадлежность исследованной группировки к сибирскому виду. EN: A molecular-genetic analysis of the nucleotide sequences of the cytochrome b gene (1140 base pairs) of mitochondrial DNA and 17 microsatellite loci of eight samples of roe deer from the Samara forest of the Dnipropetrovsk region (Ukraine) was carried out. For comparison, 212 corresponding mtDNA sequences of Siberian and European roe deer and data on the variability of microsatellite markers in 49 representatives of these species were included in the study. It was noted that all analyzed mitochondrial sequences of individuals from the Samara forest are characteristic of the Siberian roe Capreolus pygargus Pall. 1771. Four haplotypes were described, all of which belonged to the haplogroup typical for the western part of C. pygargus range. Fragment analysis of microsatellite loci of nuclear DNA confirmed the belonging of the investigated group to the Siberian species
Siberian Roe Deer (Capreolus pygargus Pallas, 1771) in Ukraine: the Analysis of Mitochondrial and Nuclear DNA
Keywords: анализ нуклеотидных последовательностей гена; косули; Capreolus pygargus Pallas; ядерная ДНК; сибирская косуля; охотоведческая проблема; C. capreolus; ген цитохрома b; гетерозиготнось